Perceived coach-created and peer-created motivational climates and their associations with team cohesion and athlete satisfaction: evidence from a longitudinal study - Garcia-Calvo, T.; Leo, F. M.; Gonzalez-Ponce, I.; Sanchez-Miguel, P. A.; Mouratidis, A.; Ntoumanis, N. (Journal of Sports Sciences, 2015)
In this longitudinal study, we examined the extent to which perceived coach- and peer-created motivational climates are associated with athlete-group cohesion and satisfaction with participation among Spanish soccer players competing in the Third National Division. Multilevel modelling analyses showed that perceived coach-created task climate was positively related to perceived cohesion and players` satisfaction with their participation within their team. Also, perceived peer-created task climate related positively to perceived cohesion. The results indicate the importance of considering peer-related aspects of the motivational climate in addition to considering the coach-related aspects of the motivational climate when examining motivational group dynamics in sport.